EFFECT OF ACADEMIC SUPERVISION AND SCHOOL CULTURE ON TEACHER’S TEACHING QUALITY IN PUBLIC ISLAMIC SENIOR HIGH SCHOOL BANJARMASIN - Mujiati, Mujiati; Suriansyah, Ahmad; Effendi, Rustam (Journal of K6, Education and Management, 2019)
The purpose of this study was to describe and analyze: (1) the effect of the principal?s academic supervision on the teacher? teaching quality in all MAN  at Banjarmasin; (2) the influence of school culture on the teacher? teaching quality in all MAN at Banjarmasin; and (3) there is the effect of principals? academic supervision and schoo culture simultaneously on the teacher? teaching quality in all MAN at Banjarmasin. This study uses descriptive quantitative methods. The study population was MAN Teachers in Banjarmasin as many as 109 teachers, as well as being used as research samples (total samples). Data was collected using a questionnaire; validity was tested using item-total correlation techniques and reliability tested using the apha formula from Cronbach. Hypothesis testing uses simple and multiple regression. The  results of the analysis conclude that: (1) there is an effect of the principal's academic supervision on the teachers? teaching quality in all MAN at Banjarmasin. This data is supported by the results of statistical analysis that prove the value of t count> t table (7.826> 1.982), (2) there is an influence of school?s culture on the teachers? teaching quality in all MAN at Banjarmasin. This data is supported by the results of statistical analysis that prove the value of t count> t table (6.428> 1.982), and (3) there is a simultaneous effect of principals' academic supervision and school?s culture on the teachers? teaching quality in all MAN at Banjarmasin. This data is supported by the results of statistical analysis that prove the value of f count > f table (10.416> 3.082). Based on those results, the headmaster is recommended to continue academic supervision to the teachers they lead and maintain the school culture in order to make the school atmospher is conducive so that the quality of teaching teachers are increased.